Spatial modeling thrips (Insecta: Thysanoptera) in growing avocado (Persea americana). (2017)
Mexico is the main producer and exporter of avocados in the world, the trips are considered a major pest of avocado in Mexico, as they feed on small fruit and form ridges or bumps which as the fruit grow they are more visible and it loses economic value. In addition to this damage, injuries caused by thrips are the main cause for presence of avocado scab. Alternative control against thrips has lacked effectiveness because their spatial distribution is unknown in avocado orchards. This study aimed to determine the spatial distribution of populations of thrips in avocado using spatial statistical techniques that led to the generation of maps through kriging. The results showed that populations of thrips present an aggregate type of distribution, which was corroborated by density maps. Infestations were distributed in 100 % of the two experimental plots, which is interesting to apply control measures only on specific areas of infestation. It was possible to determine spatial and temporal short-term stability thrips populations.